Learning-by-doing in two sectors, production structure, leisure and optimal endogenous growth - Matthias Göcke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2011)
A model with two different production sectors and endogenous growth based on the accumulation of sector-specific human capital due to learning-by-doing is presented. Accumulation of experience is measured by means of sectoral production output aggregated over time. Growth is controlled by a dynamic optimisation of the use of time for working in the different sectors or for leisure. Transitional dynamics of production growth, especially of structural change towards a 'new' sector (with relatively scarce experience), of the optimal sectoral distribution of working time and of leisure as well as the corresponding steady state levels are derived and a numerical simulation is performed.
Keywords: C61; D90; J22; O41; 330; Neue Wachstumstheorie; Mehr-Sektoren-Modell; Humankapital; Lernprozess; Arbeitszeit; Freizeit; Zeitverwendung; Theorie